The Design of Fiscal Adjustment Strategies in Botswana, Lesotho, Namibia, and Swaziland - Zanna, Luis-Felipe (IMF Working Papers; Working Paper ;, 2011)
Botswana, Lesotho, Namibia, and Swaziland face the serious challenge of adjusting not only to lower Southern Africa Customs Union (SACU) transfers because of the global economic crisis, but also to a potential further decline over the medium term. This paper assesses options for the design of the needed fiscal consolidation. The choice among these options should be driven by (i) the impact on growth and (ii) the specificities of each country. Overall, a focus on government consumption cuts appears to minimize the negative impact on growth, and would be appropriate given the relatively large size of the public sector in each country.